Lethal clinical outcome and chemotherapy and immunotherapy resistance in patients with urothelial carcinoma with MDM2 amplification or overexpression - Weijuan Zhang; Jiejie Xu; Hailong Liu; Yu Zhu; Zewei Wang; Han Zeng; Zhaopei Liu; Yuan Chang; Le Xu; Kaifeng Jin; Jingtong Xu; Xiaohe Su; et al. (Journal for ImmunoTherapy of Cancer)
Background The E3 ubiquitin ligase murine double minute 2 (MDM2) binds the p53 transcriptional activation domain and acts as a potent inhibitor of TP53 pathway, one of the three most crucial oncogenic pathways in urothelial carcinoma (UC). However, the clinical significance and impact on tumor immune contexture of MDM2 amplification in UC remain unclear.Methods This study analyzed 240 patients with UC with matched clinical annotations from two local cohorts (ZSHS cohort and FUSCC cohort). We assessed the correlation between MDM2 status and clinical outcomes, therapeutic efficacy, and immunological characteristics by immunohistochemical analysis and targeted sequencing. Additionally, 2264 UC samples from five independent external cohorts, with genomic, transcriptomic, and clinical data, were used for validation.Results MDM2 amplification (MDM2Amp) or protein overexpression (MDM2OE) was associated with inferior overall survival (ZSHS cohort, Log-rank p<0.001; FUSCC cohort, Log-rank p=0.030) and reduced response to platinum-based chemotherapy (ZSHS cohort, Log-rank p<0.001) as well as anti-PD-1/PD-L1 immunotherapy (FUSCC cohort, Log-rank p=0.016) in patients with UC, irrespective of TP53/p53 status. MDM2 amplification or overexpression was further linked to high-grade UC tumors with dedifferentiated morphology. In addition, UC with MDM2 amplification or overexpression was associated with an immuno-evasive contexture characterized by lower proportion of tertiary lymphoid structure infiltration, lower abundance of CD8+ T cells, IFN-γ+ cells, GZMB+ cells, and decreased expression of immune checkpoint molecules including programmed death-ligand 1 (PD-L1), programmed death-1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4).Conclusions MDM2 amplification or overexpression defines a lethal subset of patients with UC with inferior prognosis and resistance to both platinum-based chemotherapy and immunotherapy irrespective of TP53/p53 status. These tumors are characterized by dedifferentiated morphology and an immunosuppressive microenvironment. Accurate assessment of MDM2 status can improve risk stratification and enable personalized genomics-guided treatment for patients with UC.